Level and Capacity Assessment of Technological Development of Enterprise - Mikaeva, S.A.; Mikayeva, A.S. (International Journal of Engineering and Technology, 2018)
This article assesses the technological level and potential of technological development of an enterprise on the basis of a methodical approach. The essence of this approach is to build a composite indicator of the object being evaluated by determining its key components. First, there is a process of decomposing the summary indicator in order to determine the quantitative indicators of its constituent elements, and then, aggregating the obtained values into a composite index in order to obtain a generalized assessment.